Effects of short-term aerobic exercise on creativity. (June 2022) - Zhao, Yuan; Qin, Chuan; Shu, Deming; Liu, Dianzhi
Highlights: Fully explored the effects of short-term aerobic exercise on convergent creativity and divergent creativity. College students were divided into regular-exercisers and light-exercisers for comparison. Through the influence of aerobic exercise on creativity, some practical suggestions are put forward. Abstract: Creativity refers to the ability of individuals and groups to produce new, unique and valuable ideas or products, which can be divided into convergent creativity and divergent creativity. For college students, short-term aerobic exercise not only improves physical fitness but is also a key factor affecting creative performance, which is of great significance to their study and life. However, it is still worth exploring whether this promotion occurs immediately and can be sustained over a period of time. To comprehensively investigate the effects of short-term aerobic exercise on creativity, we conducted two studies. In study 1, 50 undergraduates completed a convergent creativity test (Chinese compound remote associate problems, CCRA) and a divergent creativity test (alternates uses task, AUT) before (pretest) and after 25 min (posttest) of short-term aerobic exercise. In study 2, 55 undergraduates were recruited to complete the same pretest and posttest as in study 1, except that they completed the posttest 30 min after finishing short-term aerobic exercise. The results showed that short-term aerobic exercise immediately improved the performance of convergent creativity and divergent creativity but not after a 30 min delay. The research results provide practical guidance for the improvement of college students' creativity and academic performance.